IDENTIFIKASI PENGETAHUAN METAKOGNISI SISWA KELAS XI MIA SMAN 2 KOTA JAMBI BERDASARKAN GAYA BELAJAR DALAM PEMECAHAN MASALAH MATEMATIKA - Silvia Fitriani; Seila Cahyani Rahmawati; ayu yarmayani (PHI: Jurnal Pendidikan Matematika, 2017)
The purpose of this study was to identify students' metacognition knowledge based on VAK learning styles (visual, auditorial, and kinesthetic) in mathematical problem solving. The type of research used is qualitative research using descriptive qualitative research method. Research subjects are all students of class XI MIA SMA Negeri 2 Kota Jambi with the number of students 192 people. Of the total students of class XI MIA will be selected 3 people as informants. Methods of data collection in this study is a questionnaire learning style, mathematical problem solving, and interview guidelines. The required data is obtained through mathematical problem solving test and interview guidance validated by the validator. Questionnaire learning style used to find the subject to be identified has been validated by a team of experts who are in UPBK UNJA. Data analysis techniques used Milles and Huberman analysis which included (1) data reduction, (2) data presentation, and (3) verification and conclusion. The results showed that students with visual, auditorial and kinesthetic learning styles have met all metacognition knowledge indicators, namely declarative knowledge, proedural knowledge, and conditional knowledge in each polya cale stages, that is understanding the problem, preparing the plan, executing the plan and checking again. This can be seen from the student's answer sheet and reinforced by the interview result done after working on problem solving.Keywords: Knowledge Metacognition, Learning Styles, Mathematical Problem Solving